Surface-enhanced Raman spectroscopy and fluorescence spectroscopy towards detection of pterins - Smyth, Ciarán (Trinity College (Dublin, Ireland). School of Physics, 2013)
In this thesis, a preliminary study is conducted into surface-enhanced Raman spectroscopy (SERS) and fluorescence spectroscopy towards the detection and analysis of pterins. Firstly, investigation of some optical properties of various pterin species is considered, using absorption and fluorescence spectroscopy. Silver colloids for SERS anlaysis are then investigated, particularly concerning substrate reproducibility and analysis optimisation. Complementary to the study of using silver colloids is the investigation of SERS using two nanoparticulate substrates, prepared using pulsed laser deposition (PLD) and electron beam evaporation (EBE). These materials are also characterised according to their SERS reproducibility and the PLD films are compared to a commercial substrate. The appendices consider other materials and techniques used during the project, and an outlook for future work is also presented.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin